The Role of Product Quality and Brand Image on Repurchase Intention Mediated by Brand Trust Among Consumers of Healthy Food Products - Finetta Rizkya Arzety; Murry Harmawan Saputra; Dedi Runanto (Majapahit Journal of Islamic Finance and Management, 2026)
The rapid growth of the healthy food industry in Indonesia has increased competition, making it important for companies to understand the factors influencing consumers’ repurchase intention. This study aims to examine the effects of product quality and brand image on repurchase intention, with brand trust as a mediating variable, among consumers of Hotto healthy food products. A quantitative approach was employed using a survey of 130 consumers. Primary data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that product quality and brand image have positive and significant effects on repurchase intention. Both variables also positively and significantly affect brand trust. In addition, brand trust positively influences repurchase intention and significantly mediates the relationships between product quality, brand image, and repurchase intention. These findings suggest that maintaining product quality, strengthening brand image, and building consumer trust are essential strategies for increasing repeat purchases. This study contributes to the marketing literature by confirming the mediating role of brand trust in explaining repurchase intention in the healthy food industry.